European Collection Resources - museums serving European identity - Šola, Tomislav (Array, 2010)
The paper present a problem of what stands behind objects of museum collections and the stories told through them. It aims to answers the question of how collections respond to the needs of the public, and if the can do so. The conclusion is that disappearing cultures cannot be preserved simply by collecting objects and that redefinition of collecting, research and communication is needed.